2018
DOI: 10.29333/ejgm/93135
|View full text |Cite
|
Sign up to set email alerts
|

The factors affecting the waiting time of outpatients in the emergency unit of selected teaching hospitals of Tehran

Abstract: Background and Objective: Long stops in the emergency unit will result in patient dissatisfaction and increased casualties. The present study aimed to determine the waiting time of patients visiting the emergency unit of two selected teaching hospitals in Tehran and the factors affecting it. Methodology: The present research was a cross-sectional descriptive-analytic study which was conducted in 2016. The statistical population included all patients and their caregivers in the emergency unit of Mofid and Ali A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…to understa ng, including a shortage of doctors. These ndings align with other studies conducted in Iran by [22], which revealed similar factors contributing to prolonged patient wait times. These factors included a high patient volume, long distances between emergency units, poor communication, and insu cient manpower.…”
Section: Waiting Timesupporting
confidence: 92%
See 2 more Smart Citations
“…to understa ng, including a shortage of doctors. These ndings align with other studies conducted in Iran by [22], which revealed similar factors contributing to prolonged patient wait times. These factors included a high patient volume, long distances between emergency units, poor communication, and insu cient manpower.…”
Section: Waiting Timesupporting
confidence: 92%
“…Factors such as the large number of patients, long distance between emergency units, poor communication, and the low number of human resources affect the prolonged patient waiting time [22]. Another study found that poor management, lack of coordination, and inadequate resources were associated with long waiting times in the ED [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Additional factors include physician level and experience, shortage of medical resources, poor communication either between staff or with the patient, and delays in physician attendance. 13 For decision to disposition time, the third indicator was mean (58.51) STD (166.30) minutes. This interval, known as ED boarding-which refers to the time after the patient has completed ED care and is waiting for an inpatient bed-has a strong relation to inpatient services and availability of beds.…”
Section: Discussionmentioning
confidence: 99%
“…The time to disposition decision is influenced by a number of other factors in addition to overcrowding, such as the availability of medical resources, physician attendance, delays in consultation by other medical staff, the level of experience of the attending physician, and the ease of staff and patient communication. 25 , 26 These factors might explain the distinct findings in our study.…”
Section: Discussionmentioning
confidence: 70%